PEMANFAATAN TEKNOLOGI DALAM BIDANG EVENT MANAGEMENT KAJIAN: PERSEPSI MAHASISWA MELALUI TECHNOLOGY ACCEPTANCE MODEL (TAM) - Enricho Gabriel Masahengke Masahengke; Mohamad Rafif Zulfiqar; Christiano Joviel Budi Pradigda; Aditya Rizki Rinaldi (MEDIANTARA: Indonesian Journal of Creative Business and Technology (IJCBT), 2026)
This study aims to analyze the perception of students at Multimedia Nusantara Polytechnic (MNP) regarding the use of technology in Event Management programs using the Technology Acceptance Model (TAM). The study focuses on Perceived Usefulness (PU), Perceived Ease of Use (PEOU), Perceived Enjoyment (PE), Self-Efficacy (SE), Personal Innovativeness in IT (PII), and Behavioral Intention to Use (BII) to evaluate students’ readiness for digital transformation and technological proficiency. Data were collected through an online questionnaire from 78 Event Management students with relevant experience in technology usage. The analysis was conducted using descriptive statistics and Structural Equation Modeling with Partial Least Squares (SEM-PLS). The results indicate that students hold highly positive perceptions of the usefulness, ease of use, and enjoyment of technology, along with high confidence in their ability to operate it. Personal Innovativeness in IT significantly affects Self-Efficacy but does not directly influence PU, PEOU, or BII. PU and PE were found to be the dominant factors driving students’ intention to use technology in learning and professional practice. These findings highlight that MNP’s vocational education approach effectively prepares students to become adaptive human resources, capable of embracing digital transformation and optimizing technology utilization in professional and daily life contexts. This study provides implications for developing other vocational education programs to enhance workforce readiness in the digital era.